Use of Sildenafil in Pulmonary Arterial Hypertension: Findings from a U.S. Healthcare Claims Database - Ariel Berger; John Edelsberg; Simon Teal; Marko A. Mychaskiw; Gerry Oster (Journal of Health Economics and Outcomes Research)
**Background:** Pulmonary arterial hypertension (PAH) is a disease characterized by dyspnea, fatigue, chest pain and syncope. As there is no known cure for PAH, the goal of treatment is to control symptoms and slow disease progression. Sildenafil, a phosphodiesterase-5 inhibitor, has been indicated to improve exercise capacity in PAH in both the United States and the European Union since 2005; since 2009, it also has been indicated in the United States to delay clinical worsening. Patterns of sildenafil use in PAH patients have not been reported.